2021
DOI: 10.1101/2021.07.07.21260151
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors for SARS-CoV-2 seroprevalence following the first pandemic wave in UK healthcare workers in a large NHS Foundation Trust

Abstract: BackgroundWe aimed to measure SARS-CoV-2 seroprevalence in a cohort of healthcare workers (HCWs) during the first UK wave of the COVID-19 pandemic, explore risk factors associated with infection, and investigate the impact of antibody titres on assay sensitivity.MethodsHCWs at Sheffield Teaching Hospitals NHS Foundation Trust (STH) were prospectively enrolled and sampled at two time points. SARS-CoV-2 antibodies were tested using an in-house assay for IgG and IgA reactivity against Spike and Nucleoprotein (sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In addition, the importance of asymptomatic transmission was increasingly appreciated and twice weekly lateral flow testing for healthcare workers was introduced in December 2020. Furthermore, seroprevalence rates of over 25% have been reported in HCWs following the first pandemic wave, [26] including in our NHS Trust, [27] which may have contributed to greater protection and reduced transmission in some areas. For example, we have reported that the SARS-CoV-2 seroprevalence in staff working on our acute medical unit by June 2020 was over 40%.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, the importance of asymptomatic transmission was increasingly appreciated and twice weekly lateral flow testing for healthcare workers was introduced in December 2020. Furthermore, seroprevalence rates of over 25% have been reported in HCWs following the first pandemic wave, [26] including in our NHS Trust, [27] which may have contributed to greater protection and reduced transmission in some areas. For example, we have reported that the SARS-CoV-2 seroprevalence in staff working on our acute medical unit by June 2020 was over 40%.…”
Section: Discussionmentioning
confidence: 95%
“…For example, we have reported that the SARS-CoV-2 seroprevalence in staff working on our acute medical unit by June 2020 was over 40%. [27] This was an area which was a hotspot for transmissions involving staff during our Wave 1 analysis but had very few transmission events identified during Wave 2.…”
Section: Discussionmentioning
confidence: 99%
“…It has good internal consistency, Cronbach's α = 0.89 [32]. The intensity of anxiety symptoms can be classified as minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), or severe (15-21 points). Depression.…”
Section: Methodsmentioning
confidence: 99%
“…Healthcare workers (HCW) are at the forefront of dealing with the pandemic; they share in the burdens borne by everyone (e.g., curfews, restrictions in activities), but in addition, face specific stressors due to their profession (e.g., increased risk of infection, increased workload). Even though some researchers did not find evidence that more exposure to COVID-19 patients conferred a higher risk of infection in this group [1][2][3][4][5], there is strong evidence for markedly increased rates of COVID-19 in HCW compared to the general public [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…While physical therapists are particularly in close contact with COVID-19 patients, they are usually underrepresented (if at all considered) in HCW seroprevalence studies [14] , [15] . A large US study supported by the Centers for Disease Control found the highest seroprevalence rates amongst nurse assistants (12.8%) and physical therapists (10.6%; [14] , and a study in the UK described physiotherapists as the group with the second-largest infection risk (39% seropositive), right after ICU staff (41%; [16] .…”
Section: Introductionmentioning
confidence: 99%